2012
DOI: 10.1002/bjs.8884
|View full text |Cite
|
Sign up to set email alerts
|

Staging and outcome depending on surgical treatment in adenocarcinomas of the oesophagogastric junction

Abstract: Accurate preoperative staging of AOG and appropriate surgical therapy are crucial for outcome. AOG type II is a more aggressive tumour with higher recurrence rates than AOG type I. These patients therefore benefit from more radical surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
2
18
0
7
Order By: Relevance
“…), [6][7][8][9]16,18 which was confirmed in this study. Several studies, including this present study, report that the stations with the most affected lymph nodes are the paracardial and lesser curvature stations.…”
Section: Discussionsupporting
confidence: 89%
“…), [6][7][8][9]16,18 which was confirmed in this study. Several studies, including this present study, report that the stations with the most affected lymph nodes are the paracardial and lesser curvature stations.…”
Section: Discussionsupporting
confidence: 89%
“…We have further demonstrated that survival is worse for more distal tumours; patients with pathologically defined Type III tumours are less than half as likely to be alive at 3 years when compared to distal oesophageal tumours. We are not the first to report a biological difference between tumours at the GOJ 2 , 3 , 5 , 36 . In our series, Type III tumours were larger and they were associated with more frequent evidence of perineural and vascular invasion, although this did not translate into more lymph node metastasis.…”
Section: Discussionmentioning
confidence: 76%
“…This series also highlights one of the major problems with the Siewert classification, the relative inability of experienced oesophageal physicians to accurately distinguish the epicentre of tumours around the GOJ on pre-operative assessment 5 , 29 . In our cohort, 42% of pathologically proven Type III tumours were designated as more proximal disease during the pre-operative work-up.…”
Section: Discussionmentioning
confidence: 96%
“…Another study compared patients initially classified as AEG I and resected by esophagectomy, who turned out to be AEG II in the histopathological report, to patients with AEG type II and resection by THG. Within this study the patients after gastrectomy survived longer [36]. A recently published study also compared thoracic and abdominal approaches for AEG II and III without differences in overall survival, R0 resection rate, and number of removed lymph nodes, but the authors demonstrated a survival benefit after an extended abdominal lymphadenectomy (D2) [52].…”
Section: Discussionmentioning
confidence: 97%
“…Despite multiple studies [8,[35][36][37][38][39][40], the discussion is still ongoing whether the "true" carcinoma of the cardia should be resected in accordance to a carcinoma of the esophagus or stomach. Most of the studies are of a heterogeneous design, summarizing different surgical approaches under esophagectomy and gastrectomy and including not only AEG II but AEG I-III.…”
Section: Discussionmentioning
confidence: 99%